1996
DOI: 10.1099/13500872-142-5-1191
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of iron by the non-siderophore-producing Pseudomonas fragi

Abstract: The iron requirement, siderophore production and iron uptake mechanisms of the type strain Pseudomonas fragi ATCC 4973 and five P. fragi isolates from meat were analysed. The strains exhibited a high sensitivity to iron starvation: their growth was strongly inhibited in medium supplemented with the iron chelator ethylenediamine di(hydroxypheny1acetic acid) or in medium treated with 8-hydroxyquinoline to remove contaminating iron. No siderophores were detectable in the growth supernatants of iron-starved cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 64 publications
(92 reference statements)
0
35
3
Order By: Relevance
“…This suggests that active factors in these extracts are siderophores which have stimulatory functions on the growth of V0210. Although growth stimulation of some terrestrial bacteria has been reported by the addition of exogenous siderophores (6,8,21), it is not clear whether those bacteria might have been stimulated to synthesize their own siderophores. Paper electrophoresis of siderophore extracts from V0210 cultures showed that the CAS-positive component was produced only after cultivation with each of the exogenous siderophores from the four Sid ϩ strains, V0122, V0304, V0902, and V1110.…”
Section: Bacteria Were Sidmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that active factors in these extracts are siderophores which have stimulatory functions on the growth of V0210. Although growth stimulation of some terrestrial bacteria has been reported by the addition of exogenous siderophores (6,8,21), it is not clear whether those bacteria might have been stimulated to synthesize their own siderophores. Paper electrophoresis of siderophore extracts from V0210 cultures showed that the CAS-positive component was produced only after cultivation with each of the exogenous siderophores from the four Sid ϩ strains, V0122, V0304, V0902, and V1110.…”
Section: Bacteria Were Sidmentioning
confidence: 99%
“…All procedures were performed according to the method of Champomier-Verges et al (6). After cultivating bacteria in iron-replete or iron-deficient media for 48 h, cells from 5-ml cultures were harvested by centrifugation and then resuspended in microcentrifuge tubes in 1 ml of 50 mM Tris-HCl-0.5 mM MgCl 2 buffer, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, siderophores produced by one micro-organism can be taken up by another. For instance, Arthrobacter flavescens is able to take up siderophores made by soil fungi and bacteria (Winkelmann, 1991), and the non-siderophore-producing Pseudomonas fragi uses exogenous siderophores, such as ferrioxamine, enterobactin and some pyoverdines, for its Fe nutrition (Champomier-Verges et al, 1996). Exogenous siderophores, such as cepabactin and coprogen, promote Fe uptake by Pseudomonas aeruginosa PAO1, while others, such as ferrichrome A, have no effect on its Fe nutrition, indicating the requirement for specific siderophore transporters (Meyer, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, presumably not just simple iron deficiency induces the vibE homologue, but a combination of a lack of iron and the presence of other components of the AH2 supernatant is required to induce the vibE homologue. From other studies (8,16) siderophores are known to positively affect the growth of bacteria other than the siderophore-producing organism. The examples include specific cross feeding (16) or stimulation of a non-siderophore-producing bacterium by addition of siderophore-containing supernatants from another producing organism (8).…”
Section: Discussionmentioning
confidence: 99%
“…From other studies (8,16) siderophores are known to positively affect the growth of bacteria other than the siderophore-producing organism. The examples include specific cross feeding (16) or stimulation of a non-siderophore-producing bacterium by addition of siderophore-containing supernatants from another producing organism (8). Although growth of V. anguillarum is inhibited after exposure to the siderophore-containing AH2 supernatant, the presence of siderophores of strain AH2 origin might positively affect the V. anguillarum siderophore synthesis apparatus, leading to production of novel V. anguillarum siderophores (e.g., anguibactin) and hence induction of the vibE homologue.…”
Section: Discussionmentioning
confidence: 99%